The Concept of Islamic Science According to Alparslan Acikgenc: A Study on Contemporary Islamic Epistemology - Widodo, Chandra Dwisetyo; Arif, Syamsuddin; Ahmed, Ashadulla S (LPPPM STAI Darul Hikmah Bangkalan, 2024)
This article delves into the concept of Islamic science as articulated by Alparslan Acikgenc, a contemporary issue in Islamic epistemology. The study is set against the backdrop of the impact of secular Western science and the dominance of the Western modern science paradigm, rooted in Western philosophy, values, and culture. This context highlights the fact that science is not neutral but inherently value-laden, which calls for a deeper exploration and development of Islamic science. Alparslan Acikgenc, a notable Islamic scholar, provides a definition of Islamic science that is intricately linked to the Islamic worldview, which serves as a fundamental framework for Islamic science. Utilizing descriptive and analytical methods, this study draws several important conclusions. Firstly, Alparslan posits that a scientist's worldview is inseparable from the science they produce, indicating that the underlying beliefs and perspectives of scientists shape their scientific output. Secondly, he argues that a systematic Islamic worldview is necessary for the development of Islamic science, suggesting that without this foundational basis, the science produced will not align with Islamic principles. Thirdly, Alparslan acknowledges that while these definitions are not universally absolute, they hold conventional universality. This means that despite potential differences in opinions among scientists, as long as they share the same worldview, the resulting science will be consistent and coherent. This research underscores the importance of developing Islamic science within its own epistemological framework, thereby challenging the hegemony of Western scientific paradigms and highlighting the significance of cultural and philosophical values in shaping scientific knowledges.